Smart Enterprise in HRIS at University of Phayao - Wongpanya Nuankaew, Pratya Nuankaew, Ronnachai Thipmontha, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The objective of this research is to analyse and design huge of the personal data components in government organizations that are management issues in human resource planning. It has three essential components: The first component is to study the problematic elements regarding management and the conception of a personal development plan. The second component is the development of a database system to be used to drive the smart enterprise. The third component is the evaluation of the developed database system. This research is a qualitative research. There were 21 samples used to evaluate the database. It consists of executives and staff who are involved in the development of the human resource planning. The tool used in this research consists of two parts. The first part is database design and development tools. The second part is the database design evaluation tools. It consists of the satisfaction questionnaire for database design, and the database performance assessment form. The statistics used in the research were mean and standard deviation. The researchers were found that the results of the evaluation of database design were at the highest satisfactory level (x ̅=4.60). The evaluation results of the database user interface design were found at the highest level (x ̅=4.59). The evaluation results of the utilization expectation of the database system were found at the highest level (x ̅=4.73). For future work, the researcher aims to develop it into a mobile application to facilitate further.